Malpositioned olecranon fracture tension-band wiring results in proximal radioulnar synostosis. Issue 1 (December 2015) - Willinger, Lukas; Lucke, Martin; Crönlein, Moritz; Sandmann, Gunther; Biberthaler, Peter; Siebenlist, Sebastian
Abstract Background Tension-band wiring (TBW) is a well-established fixation technique for two-part, transverse fracture types of the olecranon. However, complication rates up to 80 % are reported. By reporting on the enormous impact on the patient if failed the aim of the present report was to emphasize the importance of correct K wire positioning in TBW. Case presentation We present the case of a 49-year-old woman who suffered from a radioulnar synostosis of the forearm due to malpositioned K wires after TBW treatment. The patient was treated by heterotopic bone resection supported by ossification prophylaxis (radiotherapy and Indomethacin). At follow-up of 12 months after revision surgery, elbow motion was unrestricted with a strength grade 5/5. The patient was free of pain and reported no restrictions in daily as well as sporting activities. Radiologic assessment showed no recurrence of heterotopic bone tissue. Conclusion Intraoperative radiographic and clinical examination of the elbow is highly recommended to identify incorrect hardware positioning and, therefore, to avoid serious postoperative complications in TBW.